Efektivitas Penambahan Suplementasi Vitamin C Terhadap Penurunan Malondialdehid dan Perbaikan Derajat Aktivitas Penyakit Lupus Eritematosus Sistemik: Uji Klinis Acak Tersamar Ganda - Yuniza, Yuniza; Kurniati, Nova; Theodorus, Theodorus; Salim, Eddy M; Hartanto, Kristian S (Jurnal Penyakit Dalam Indonesia, 2026)
Introduction. Vitamin C is an antioxidant that exerts its effects at multiple cellular levels. However, evidence regarding its effects in systemic lupus erythematosus (SLE) remain inconclusive. This study aimed to evaluate the potential of vitamin as an adjunctive antioxidant therapy in patients with SLE by assessing its effects on serum malondialdehyde (MDA) levels and disease activity using the Mexical Systemic Lupus Erythematosus Disease Activity Index (MEX-SLEDAI) score. Methods. This pilot double-blind, randomized controlled trial was conducted at Dr. Mohammad Hoesin General Hospital, Palembang. Participants were patients with mild-to-moderate SLE diagnosed according to the 2019 European Alliance of Association for Rheumatology/American College of Rheumatology (EULAR/ACR) classification criteria and assessed using the MEX-SLEDAI score. Subjects were randomly assigned to receive either vitamin C (500 mg twice dailiy for 2 months) or placebo in addition to standard SLE therapy. Serum MDA levels and MEX-SLEDAI scores were measured at baseline and after the intervention. Results. A total of 34 subjects were enrolled in the study. The mean baseline serum MDA concentration was 1.38 (SD 0.31) μmol/L. After 2 months of treatment, the vitamin C group demonstrated a significant reduction in serum MDA levels [1.38 (SD 0.38) μmol/L vs. 1.09 (SD 0.26) μmol/L; p = 0.003] and MEX-SLEDAI scores [median 2 (2–5) vs. 1 (0–2); p = 0.001]. In the placebo group, only the MEX-SLEDAI score decreased significantly [3 (2–7) vs. 2 (0–6); p = 0.016], whereas serum MDA levels showed no significant change [1.37 (SD 0.25) μmol/L vs. 1.32 (SD 0.38) μmol/L; p = 0.518]. Between-group comparisons revealed that both the reduction in MDA (p = 0.047) and MEX-SLEDAI (p=0.048) were significantly greater in the vitamin C group compared to placebo group. Conclusions. Vitamin C supplementation at dose of 500 mg twice daily as an adjuct to standard therapy could reduce disease activity and serum MDA levels in patients with mild-to-moderate SLE.